(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article proposes a reflection on how the exercise of lovingness can help in transforming oneself, understanding the importance of collaborative work and expanding the creative possibilities in the actor’s work. The researcher, teacher of body disciplines in theater colleges, noticed that there is a significant change in the relationships between students, inside and outside the classroom after performing practices through the study of milenar hindu theory of chakra system, focusing on the heart chakra. Will be presented suggestions of exercises, quotes from students’ perceptions and reflections from the practices of lovingness.